Pharmacological Review on Astragalus membranaceus: Chinese Traditional Herb - Ikbal, Abu Md Ashif; Rajkhowa, Amlanjyoti; Debnath, Bikash; Singh, Waikhom Somraj; Manna, Kuntal; Bhattacharjee, Bedanta; Das, Tanmoy; Goswami, Sanchari (Pharmacognosy Reviews)
Astragalus membranaceus is a Chinese medicinal plant belonging to the family Leguminosae. This plant is actively used in traditional Chinese medicine for its diverse therapeutic application. The plant contains various active phytochemicals that produce various pharmacological activities. From the literature review, the essential pharmacological activities of Astragalus membranaceus are reduce oxidative stress, neuroprotective, antiviral, anti cancer, immunomodulatory, vascular protective, and antimicrobial activities. In this review, we summarize the pharmacological activities of Astragalus membranaceus with the proper mechanism of action.
Keywords: Phytoconstituents; Neuroprotective; Antiviral; Anti-neoplastic; Immunodulatory agent; Alzheimer; Cardioprotective